ANALISIS PERSEPSI HAK INDIKASI GEOGRAFIS SALAK PONDOH PADA KOMUNITAS AGROWISATA DI KABUPATEN SLEMAN - susilo budi winarno; Tuti Panghastuti (Fakultas Pariwisata Universitas Pancasila, 2020)
Geographical Indication of Agro-tourism is a unique tourism activity to areas or rural locations whose products are already known to have superior quality and characteristics.